Pencatatan Pelaporan Keuangan Pada PT Kawan Bisnis Sejati Menggunakan Aplikasi Zahir Accounting 5.1 - Auliani, Faulhia; Saputra, Elin Panca; Priyono, Priyono; Dwiantoro, Tino; Elin Panca Saputra, panca (LPPM Universitas Bina Sarana Informatika, 2024)
An application that is common nowadays in many institutions, service companies that use it, because information technology is developing so quickly. The aim of this paper is to implement the use of accounting applications to reduce errors in recording large amounts of financial reporting at PT. A True Business Friend. As for PT. Sejati Business Friends really needs a change in the information system to support and make it easier for finance employees to work. For this reason, we created an implementation regarding a financial recording system using an accounting-based application at PT. True Business Friends which until now has not been computerized. So there are many obstacles faced by PT. True Business Friends in financial reporting where there are often differences in the amount of income and financial expenditure which can be detrimental to PT. A True Business Friend. So, to overcome the problems above, we suggest that there is a need for changes in managing PT's financial system. A True Business Friend. Namely implementing Zahir Accounting version 5.1 to support operations, especially in recording large amounts of finance in financial management. By implementing Zahir Accounting, the financial reporting system becomes more accurate and minimizes errors in recording financial reports..